Strategi Pemahaman Membaca Bahasa Arab di MA Darul Mukhlasin Tegalsiwalan (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
Reading comprehension in Arabic is an essential skill for students at MA Darul Mukhlasin Tegalsiwalan. This ability supports the understanding of religious texts and enhances overall language competence. This study aims to analyze the strategies implemented to improve Arabic reading comprehension at the madrasa. This research employs a qualitative approach with a descriptive method. Data were collected through classroom observations, interviews with Arabic teachers, and analysis of learning documents. The study focuses on the teaching strategies applied, the challenges encountered, and the effectiveness of the methods in enhancing students' reading comprehension. The findings indicate that the strategies used at MA Darul Mukhlasin Tegalsiwalan include the talaqqi method, authentic text-based learning, and a contextual approach. These strategies effectively help students comprehend the meaning and increase their interest in learning. However, some challenges persist, such as the limited availability of diverse reading materials and restricted learning time allocation. Evaluating and developing more innovative methods is expected to further enhance students' Arabic reading comprehension at the madrasa.